HOW TRANSFORMATIONAL LEADERSHIP INTENSIFY EMPLOYEE PERFORMANCE MEDIATING BY JOB SATISFACTION - IGede Putu Kawiana; I Gede Riana; I Gede Rihayana; I Nyoman Rasmen Adi (Universitas Mercu Buana, 2020)
These studies aimed to investigate the relationship between transformational leadership on job satisfaction and employee performance. The study adopted a quantitative paradigm with a population of employees at the Investigation Department, Immigration Office in Bali, Indonesia. The questionnaire was spread to 253 employees on intervals time three weeks by the number was responding are 115 employees. The results revealed that transformational leadership has a significant effect on job satisfactionhowever, no significant impact on employee performance. Job satisfaction has a significant impact on employee performance. Moreover, this research found that job satisfaction played an essential role as a mediating between transformational leadership on employee performance. The implications of the study represent job satisfaction as a critical role and will be discussed. Whereas, the practical implications concern the importance of administering equity in the transformational leadership values to enhance employee performance.